The value of chest X-ray and CT severity scoring systems in the diagnosis of COVID-19: A review - Majrashi, Naif Ali A. (Frontiers in Medicine, 2023)
Coronavirus disease 2019 is caused by a coronavirus family member known as Severe Acute Respiratory Syndrome Coronavirus-2. The main laboratory test to confirm the quick diagnosis of COVID-19 infection is reverse transcription-polymerase chain reaction (RT-PCR) based on nasal or throat swab sampling. A small percentage of false-negative RT-PCR results have been reported. RT-PCR test has a sensitivity of 50-72%, which could be attributed to low viral load in test specimens or laboratory errors. In contrast, chest CT has shown 56-98% sensitivity in diagnosing COVID-19 at initial presentation and has been suggested to be useful in correcting false negatives from RT-PCR. Chest x-rays and CT scans have been proposed to predict COVID-19 disease severity by displaying the score of lung involvement and thus provide information about the diagnosis and prognosis of COVID-19 infection. As a result, the current study provides a comprehensive overview of the utility of the severity score index using x-rays and CT scan in diagnosing COVID-19 patients when compared to RT-PCR.